STRUKTUR ANATOMI DAN KUALITAS SERAT LIMA JENIS KAYU ANDALAN SETEMPAT ASAL CARITA BANTEN - Sri Rulliaty (Jurnal Penelitian Hasil Hutan, 2013)
Recently, the supply of commercial wood species was decreased significantly. The utilization of lesser known wood species is one of possible solution to improve log supply. This paper studies the anatomical properties and its fiber quality of five locally potential wood species from Carita, Banten, for utilization purposes. The anatomical properties were examined according to the IAWAI ist of microscopic features, while fiber qualities were examined based on its quality for pulp and paper. The main anatomical characteristics are: pangsor (Ficus fistulosa Reinn.) heartwood is white-straw to pale yellow, parenchyma bands and prismatics crystals present in upright cells and chambered axial parenchyma cells; jengkol (Pithecellobium rosulatum Kosterm) heartwood is creamy with parenchyma vascicentric; petai (Parkia speciosa Hassk.) beartwood is yellow whitish, parenchyma are vascicentric, aliform, and confluen; manii (Maesopsis emini Engl) heartwood is yellow brownish, parenchymas are scanty paratracheal to confluen; balsa (Ochroma pyramidale (Cavex. I amk) Urban) heartwood is creamy whitish with axial parenchyma apotrachea diffuse. Fibre quality of those five wood species are classified into quality class 1. Based on the fibre quality and for other alternative uses, the five locally potential wood are highly recommended for its intensive cultivation.